Philippine native chickens - Lambio, Angel L. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
The Republic of the Philippines is an archipelago composed of more than 7,100 islands. Many small islands and even certain areas within big islands are isolated by mountain ranges, bodies of water and inadequate transportation facilities. Despite the decades-old introduction of exotic commercial breeds and hybrids, more than 50% of the chicken population is still composed of the native and upgrade types. In recent years, there has been renewed interest in the identification, documentation and utilization of the native chickens. Several genetic groups have been identified and documented, the most studied genetic groups being 'Banaba', 'Bolinao', 'Camarines' and 'Paraoakan'. This paper presents some of the more important qualitative and quantitative traits of these four genetic groups.